A METEODEPENDENCY SYNDROM AS A REFLECTION OF ADAPTIVE CAPABILITIES OF HUMAN BODY DEPENDING ON THE LEVEL OF PHYSICAL ACTIVITY OF YOUNG PEOPLE - E. Kovalenko; O. Kovalenko; V. Moiseienko (Bogomolets National Medical University, 2015)
Summary. This article provides the evidence of the relationship between the meteodependency, as one of the indicators of adaptive reactions of the body, with physical activity and the alarming indicator for the young people. Based on a survey of people aged 17- 25 and its further analytical processing, the results showed that in the non- meteosensitive group the majority of people are engaged in physical activity and vice versa - meteosensitive group consists of people who rearly or never do sports. Perhaps, the physical activity has an adaptogenic effect on the autonomic nervous system due to an improved respiratory function and regulation of vascular tone.